Hola amigos,
Solve this question☝️. Its a linear equation.
No need to give ABSURD answers..
Attachments:
![](https://hi-static.z-dn.net/files/dd1/fb5d5f77507b7160c02f1e5cf359e431.jpg)
Answers
Answered by
6
Step-by-step explanation:
Let,
And
New equations formed :-
_______(1)
And
______(2)
Multiply (2) with 3
3(X - 2Y) = 3(2)
3X - 6Y = 6 _______(3)
Subtract (1) and (3)
3X + 8Y - (3X - 6Y) = -1 - 6
3X + 8Y - 3X + 6Y = -7
14Y = -7
Y = -7 / 14
Y = -1 / 2
Put this value in (1)
3X + 8(-1 / 2) = -1
3X - 4 = -1
3X = -1 + 4
3X = 3
X = 1
Now,
X = 1 / x
1 = 1 / x
Also,
Y = 1 / y
-1 / 2 = 1 / y
Similar questions